A facile formulation based on polyacrylate resin for SLA 3D printing - Lie, Anthony (Nanyang Technological University, 2020)
3D printing has become very relevant in our coming time. Many companies have embraced 3D printing and have even proclaimed that 3D printing would become our 4th industrial revolution. Some companies have taken an extra step and plan to introduce 3D printing technology to replace their subtractive manufacturing technology entirely. However, there are still many limitations to 3D printing which is preventing it from taking over tradition subtractive manufacturing entirely. In this project we specifically look at the 3D printing technology of Stereolithography (SLA). Over the years, SLA technology has been improving allowing for faster print times and smoother product finishes. Along with the increase in SLA technology and its variants, there is also an increase in materials available for SLA especially acrylate-based polymer resin material since they were the first materials available for SLA technology. In this project, we aim to learn some basics of material formulation and how to choose the most optimized formulation out of all the experimental formulas. Furthermore, we also tried to find a way to improve toughness for acrylate-based polymer material by the addition of plastic additives so as to improve their chances of being utilised for real-life applications. We were able to increase the toughness by a certain amount, but different situations may arise which may change the possibility of this increment being crucial into allowing the acylate-based polymer to be useful for real-life applications. Additionally, multiple characterization techniques were employed to further find more physical properties of the formulation. FTIR was utilised to find the degree of double carbon bond conversion which helps us find the approximate degree of polymerization. Thermal stability techniques like DSC and TGA were also used to find the glass transition temperature and initial decomposition temperature to determine whether our formula could be used for applications requiring high thermal stability.